The economics of fiscal federalism and local finance - Oates, Wallace E. (Northampton, MA : Edward Elgar, 1998)
This volume presents an authoritative collection of the most significant papers on fiscal federalism and local finance. In addition to some classic papers, it offers clear and insightful presentations of conventional wisdom in the field as well as recent papers which illuminate important issues and point the way to ongoing research.
Includes bibliographical references and index.
enc., 29/11/18.
Ref
Keywords: Intergovernmental fiscal relations; Local finance; Decentralization in government